2011
DOI: 10.1111/j.1654-1103.2011.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of species and plant traits in response to 20 years of grazing exclusion in subalpine grassland communities

Abstract: Question: Does long‐term grazing exclusion affect spatial patterns of canopy height, plant species and traits in subalpine grassland communities? Are spatial patterns of species and traits similarly affected by grazing exclusion? Are changes in spatial patterns of species associated with changes in species abundances? Location: Subalpine grasslands, Vercors and Oisans Mountains, Alps (France). Methods: Spatial sampling of vegetation and measurements of plant traits were carried out within nine pairs of graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
4
23
0
2
Order By: Relevance
“…Similar results were obtained in a study examining the effect of phylogenetic distance on the strength of interspecific competition: variation in the intensity of competition was strongly influenced by the monocot-eudicot evolutionary split, with monocots being weaker competitors against forbs and forbs being stronger competitors against monocots (Cahill et al 2008). Significant differences between growth forms have also been identified in the studies examining the strength of microbial feedbacks (Bartelt-Ryser et al 2005;de Kroon et al 2012), the effects of grazing (Deleglise, Loucougaray & Alard 2011), patterns of colonisation and extinction in experimentally established plant communities (Cadotte & Strauss 2011) and the ability of legumes to invade communities containing different growth forms (Turnbull et al 2005). Although the importance of growth form has been demonstrated in many studies, there is still little understanding of the actual traits that contribute to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in a study examining the effect of phylogenetic distance on the strength of interspecific competition: variation in the intensity of competition was strongly influenced by the monocot-eudicot evolutionary split, with monocots being weaker competitors against forbs and forbs being stronger competitors against monocots (Cahill et al 2008). Significant differences between growth forms have also been identified in the studies examining the strength of microbial feedbacks (Bartelt-Ryser et al 2005;de Kroon et al 2012), the effects of grazing (Deleglise, Loucougaray & Alard 2011), patterns of colonisation and extinction in experimentally established plant communities (Cadotte & Strauss 2011) and the ability of legumes to invade communities containing different growth forms (Turnbull et al 2005). Although the importance of growth form has been demonstrated in many studies, there is still little understanding of the actual traits that contribute to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among earlier studies focusing on the spatial analysis of functional trait diversity, Deleglise et al (), for the first time, explicitly showed that the intensity and range of spatial autocorrelation (i.e. spatial pattern) in community aggregated trait values differ between grazed and ungrazed habitats of subalpine grasslands, due to competition‐ mediated variation in species density, or to the post‐ grazing creation or disappearance of new vegetation patches and heterogeneity in site conditions.…”
Section: Hypothesized Relevance Of Ecological Processes To Large‐scalmentioning
confidence: 99%
“…In fact, grazing reduces species height and lateral spread differences (Deléglise et al. ) and, consequently, the ability of species to compete for light and space. Nevertheless, plant communities are affected by both equalizing and stabilizing mechanisms (Chesson ).…”
Section: Introductionmentioning
confidence: 99%